2021
DOI: 10.4155/fmc-2021-0109
|View full text |Cite|
|
Sign up to set email alerts
|

A Systematic Review of carbohydrate-based Bioactive Molecules for Alzheimer’s Disease

Abstract: The abundance, low cost, high density of functional groups and ease of purification of carbohydrates are among the most important features that make them a prime candidate for designing therapeutics. Several carbohydrate-based molecules, of both natural and synthetic origin, are known for their wide range of therapeutic activities. The incorporation of a carbohydrate moiety not only retains the pharmacological characteristics of a molecule but also improves its activity. Several sugar conjugates have been desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…AChE inhibitors had bonds with the enzyme peripheral binding site (PAS), and therefore, prevent the generation and deposition of Aβ [37] . The kinetic study above of AChE inhibition showed that our designed isatin β‐thiosemicarbazones could interact with PAS as well as CAS of AChE [2b,28a,38] . To further study of the dual action of these isatin derivatives, the amyloid‐beta protein (A β 1–42 ) anti‐aggregating activity of the most potent AChE inhibitors 4 s and 4 t was examined by the thioflavin‐T fluorescent (ThT) assay at 10 μM concentration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AChE inhibitors had bonds with the enzyme peripheral binding site (PAS), and therefore, prevent the generation and deposition of Aβ [37] . The kinetic study above of AChE inhibition showed that our designed isatin β‐thiosemicarbazones could interact with PAS as well as CAS of AChE [2b,28a,38] . To further study of the dual action of these isatin derivatives, the amyloid‐beta protein (A β 1–42 ) anti‐aggregating activity of the most potent AChE inhibitors 4 s and 4 t was examined by the thioflavin‐T fluorescent (ThT) assay at 10 μM concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibitory properties of compounds on self‐induced and AChE induced aggregation of amyloid β protein 1–40 was determined using a thioflavin T (ThT)‐based fluorescence assay [28a] . The ThT excitation/ emission was measured at 448 nm/490 nm at 48 h using a multimode plate reader (BMG Labtech Omega FLUOstar).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This included potential carrier proteins, adjuvants, and modifications of TACA antigens to improve stability, reduce hydrolytic cleavage and the cost of large-scale chemical or enzymatical synthesis [ 128 , 129 , 130 ]. Another area where carbohydrate-based conjugate vaccines find their application is the field of neurodegenerative diseases such as Alzheimer’s disease [ 131 ]. Overall, it cannot be denied that conjugate vaccines find their use in the broadest sense stretching multiple disease areas.…”
Section: Conjugate Vaccine Antigensmentioning
confidence: 99%
“…Curcumin derivatives were widely explored for their neuroprotection and therapeutic ability in neurodegenerative disorders and were found to have promising potential . The derivatives consist of a diketone structure alongside a trans double bond.…”
Section: Curcumin Derivativesmentioning
confidence: 99%